Patient and clinician views on the quality of foot health care for rheumatoid arthritis outpatients: a mixed methods service evaluation. Issue 1 (December 2016) - de Souza, Savia; Williams, Ruth; Lempp, Heidi
Abstract Background Feet are often the first site of joint involvement in rheumatoid arthritis (RA) and get progressively worse if unmanaged, leading to permanent disability and negatively impacting patients' quality of life. Podiatrists are specialists in the assessment, diagnosis and management of foot and ankle problems, however, RA outpatients often rely on referral from rheumatology clinicians to gain access to musculoskeletal podiatry services on the UK National Health Service (NHS). Therefore, the aim of this evaluation was to identify the foot health needs of rheumatoid arthritis patients and if they are being met by rheumatology clinicians. Methods A mixed methods approach was used: collecting qualitative data from patients and quantitative data from clinicians. Two focus groups were conducted with nine RA patients from a tertiary rheumatology outpatient clinic in the UK and the data were thematically analysed to inform a clinician survey. Thirteen rheumatology clinicians, from the same centre, completed the online survey. Resultant data were analysed to produce descriptive statistics. Results Patient focus group data generated four main themes: (1) need for foot health information, (2) feet ignored during routine consultations, (3) frequency of foot examination and (4) access to podiatry. Survey data highlighted that (i) 69–85 % of clinicians provided patients with foot health information sometimes, (ii) feet were examined in 47 % of routine consultations, (iii) 54 % of clinicians did not examine feet routinely because they are not included in the disease activity score with 28 joints (DAS-28), (iv) 31 % of clinicians referred patients to podiatry upon RA diagnosis, (v) 0 % of clinicians referred patients to podiatry for periodic review, (vi) 54 % of clinicians believed patients will self-report foot problems and (vii) 62 % of clinicians felt competent in foot examination. Conclusions RA patients' foot health needs were not being fully met by rheumatology clinicians. Patients want foot health information and easy access to podiatry services. Rheumatology outpatient consultations need to have a wider focus than the DAS-28 and incorporate foot examination as standard. Clinicians need to ensure they have sufficient training and follow current national foot health guidance to provide optimal foot health care and outcomes for their RA patients.